The psychological dimensions of sports injury risk: models, mechanisms, and interventions - Johnson, U.; Ivarsson, A. (Frontiers in Sports and Active Living, 2025)
Psychological factors influencing sports injury risk have received growing attention due to their potential for both prevention and rehabilitation. This mini review summarizes research related to psychological factors influencing sports injuries and strategies for their prevention. Injuries can have serious negative consequences for athletes' health and careers, as well as performance and financial implications for stakeholders. The research highlights psychological risk factors such as stress, anxiety, strong athletic identity, and pressure from coaches and teammates. The magnitude of stress responses is particularly linked to the risk of acute injuries, as outlined in Williams and Andersen's model and its evolution into the biopsychosocial framework. Recent studies have emphasized the complexity of overuse injuries, proposing multifactorial models accounting for intrapersonal, interpersonal, and sociocultural influences. Risk factors such as impaired neurocognitive functioning, academic stress, and strained coach-athlete relationships have been linked to both acute and overuse injuries. Combining psychological, physiological, and biomechanical assessments is increasingly recommended to better understand injury risk. Practical recommendations include fostering strong athlete-staff relationships, providing confidential psychological support, and integrating health education and autonomy-building into daily practice. Future research should investigate how combined psychological, physiological, and environmental factors affect injury risk. This mini review contributes to the evolving literature by highlighting how integrated psychological frameworks and intervention strategies can support evidence-based injury prevention and return-to-sport practices.